TIME TO RECOVERY FROM COVID-19 AMONG PATIENTS IN SIDOARJO REGENCY, EAST JAVA PROVINCE, INDONESIA IN 2022: Waktu Untuk Sembuh Dari COVID-19 di Antara Pasien di Kabupaten Sidoarjo, Provinsi Jawa Timur, Indonesia Pada Tahun 2022 - Farakhin, Noer; Choirul Hidajah, Atik; Gumilang, Retna; Setia Hadi, Supaat (Jurnal Berkala Epidemiologi, 2024)
Background: The SARS-CoV-2 mutation in the bodies of COVID-19 patients is a critical factor for health. Notably, in October 2022, the disease recovery rate in Sidoarjo (96.05%) was lower than the national rate (97.30%). Purpose: This study aims to identify the recovery time and its influencing factors in COVID-19 patients in Sidoarjo. Methods: The life-table method was used to conduct a survival analysis on data from the NAR COVID-19 dashboard in Sidoarjo from January 3 to August 4, 2022, which involved 20,662 respondents. Age group, sex, treatment status, and testing purpose were analyzed. Results: The majority of COVID-19 patients were females (50.30%) aged 26-<46 years (46.24%). Most patients (64.74%) chose to self-isolate, and 63.34% were screened as COVID-19 positive. On average, patients recovered within seven days of diagnosis. The Wilcoxon (Gehan) statistical test yielded a p-value of less than 0.001 for all factors at a significance level of 0.05, indicating a significant difference in the survival time distribution. The age group with the shortest median recovery time was 6-<12 years at 7.03 days, while males had a median recovery time of at 7.66 days. Patients who self-isolated had a median recovery time of 7.16 days, and those who were tested for close contact purposes had a median recovery time of 7.65 days. Conclusion: The median recovery time for COVID-19 patients post-diagnosis was seven days. There was a significant difference in recovery time among the COVID-19 patients based on age group, sex, treatment status, and testing purpose.